Home or away? Pathways to employment for the highly qualified in Armenia after the velvet revolution - Sargsyan, M.; Cairns, D. (Young, 2020)
In this article, we take a look at transitions to employment in Armenia for the highly qualified, focusing on students and graduates. Theoretically, we acknowledge the importance of insights from prior research, including the idea of the transition-to-work as a journey, with our research questions aimed at highlighting specific challenges facing Armenian youth following spatialized and sedentary transition pathways; moving abroad for work and entering the local labour market respectively. As evidence, we make use of interviews conducted with 51 young Armenians in the months that followed the Velvet Revolution of 2018. Discussion highlights factors that inhibit highly qualified youth from finding jobs at home, including perceptions of corruption in the workplace, difficulties associated with entering foreign labour markets and the salience of recent political events.